2012
DOI: 10.1096/fj.11-200923
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the β2‐α2 loop and interspecies prion transmission

Abstract: Prions are misfolded, aggregated conformers of the prion protein that can be transmitted between species. The precise determinants of interspecies transmission remain unclear, although structural similarity between the infectious prion and host prion protein is required for efficient conversion to the misfolded conformer. The β2-α2 loop region of endogenous prion protein, PrP(C), has been implicated in barriers to prion transmission. We recently discovered that conversion was efficient when incoming and host p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 54 publications
4
54
0
Order By: Relevance
“…48,52,53 Instead, the amino acid sequence of the b2-a2 loop has an important role in promoting CWD conversion of PrP C from other species. However, as the ferret and the squirrel monkey are highly susceptible to CWD infection, and neither has a b2-a2 loop that matches elk, it is clear that other PrP segments also interact during CWD conversion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48,52,53 Instead, the amino acid sequence of the b2-a2 loop has an important role in promoting CWD conversion of PrP C from other species. However, as the ferret and the squirrel monkey are highly susceptible to CWD infection, and neither has a b2-a2 loop that matches elk, it is clear that other PrP segments also interact during CWD conversion.…”
Section: Discussionmentioning
confidence: 99%
“…43 The resulting Tg(MoPrP S170N,N174T ) mice were highly susceptible to CWD infection compared to mice expressing wild type mouse PrP C . 47 Further studies utilizing mice with a well-defined loop due to a different substitution, D167S, showed that the loop conformation had no effect on CWD susceptibility, 48 as the mice had identical barriers as WT mice. Taken together, these results suggest that the 165-175 sequence similarity between cervid and host PrP, and not the secondary structure, governs CWD susceptibility.…”
Section: Structural Determinants Of Cwd Susceptibilitymentioning
confidence: 99%
“…Despite extensive investigations, the physiological function of PrP C in healthy organisms as well as the mechanistic aspects of its pathophysiological role remain elusive (4)(5)(6)(7)(8)(9). Although the PrP Sc form found in diseased tissue has been intensively studied, other approaches underline the importance of PrP C as a potential target for TSE prevention and medical intervention after outbreak of the disease (10)(11)(12), with a special focus on rigid-loop cellular prion proteins (RL-PrP C s) (11,(13)(14)(15), which are investigated in this paper.…”
Section: T Ransmissible Spongiform Encephalopathies (Tses) Includementioning
confidence: 99%
“…Despite extensive investigations, the physiological function of PrP C in healthy organisms as well as the mechanistic aspects of its pathophysiological role remain elusive (4-9). Although the PrP Sc form found in diseased tissue has been intensively studied, other approaches underline the importance of PrP C as a potential target for TSE prevention and medical intervention after outbreak of the disease (10-12), with a special focus on rigid-loop cellular prion proteins (RL-PrP C s) (11,(13)(14)(15), which are investigated in this paper.A common PrP C fold for a globular domain formed by the polypeptide segment of residues 125-228 in mouse PrP (mPrP) [see Schätzl et al (16) for the numeration in different species], with three α-helices and a short two-stranded antiparallel β-sheet, has been observed for the cellular prion proteins of all mammalian species studied so far (17-27). For WT PrP of most species, parts of the backbone amide group NMR signals of residues in a loop between a β-strand, β2, and a helix, α2, are not observable in NMR spectra recorded with aqueous solutions at pH 4.5 and 20°C at a 1 H resonance frequency of 500 MHz (or higher) because of line broadening by conformational exchange; therefore, the β2-α2 loop in these PrP C s is poorly defined in NMR structures determined under these conditions.…”
mentioning
confidence: 99%
“…45 The significance of the H2S2 loop region in interspecies prion transmission has been highlighted by another study, which points out the importance of primary sequence rather than structural similarities. 46 Furthermore, correlation of multiple amino acid residues with the murine-rabbit 'species barrier', suggests that primary sequence differences between interacting PrP isoforms may be associated with conversionincompatible structures. 47 Studies on heterologous PrP interactions revealed altered molecular associations 42,48 and lower conversion efficiencies.…”
Section: Discussionmentioning
confidence: 99%